Revisiting Baru Pelepat - Yuliani, E.L.; Moeliono, M.; Kusumanto, T.; Marzoni; Permatasari, E.; Adnan, H.; Indriatmoko, Y.; Colfer, C.J.P. (Routledge, 2023)
This chapter by Yuliani et al. begins with a brief description of the Adaptive Collaborative Management process that occurred in the early 2000s in the village of Baru Pelepat in Jambi province, Indonesia – a process facilitated by these authors. After a brief introduction to the community itself, Yuliani et al. launch into a description of the bottom-up process that resulted in local communities getting legal rights to manage a special forest area near their community, an area that had been part of Indonesia’s forest estate. After explaining their methods, they provide the results of a land use land cover change study, which clarifies the condition of that forest, as well as the surrounding countryside, as it has changed over the previous two decades. Building on their long-term involvement in the community, they examine decision-making, inclusivity and conflict management in the community; and then show how important decisions were made, based on ongoing community monitoring. The roles of gender, economics, biodiversity and collective action are further discussed. The chapter concludes with a discussion of the critical role of learning, in both the successes the community experienced and the skills that remain.